2022
DOI: 10.21079/11681/45143
|View full text |Cite
|
Sign up to set email alerts
|

Technical assessment of the Old, Mississippi, Atchafalaya, and Red (OMAR) Rivers : geomorphic assessment

Abstract: This report documents the geomorphic assessment component of the Old River, Mississippi River, Atchafalaya River, and Red River System Technical Assessment. The overall objectives of the geomorphic assessment are to utilize all available data to document the historic trends in hydrology, sedimentation, and channel geometry for the rivers in the vicinity of the Old River Control Complex and to summarize the changes observed at locations where repetitive datasets exist and at key reaches that are determined duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…• The history of water diversion in the vicinity of the current location of the ORCC is long and varied. This is discussed in detail in the morphological analysis report associated with this study (Lauth et al 2022). However, each of these changes in the location and distribution of water and sediment diversion has resulted in morphodynamic changes in the Mississippi River.…”
Section: Implications Of the Theoretical Analysis For The Analysis Of...mentioning
confidence: 86%
“…• The history of water diversion in the vicinity of the current location of the ORCC is long and varied. This is discussed in detail in the morphological analysis report associated with this study (Lauth et al 2022). However, each of these changes in the location and distribution of water and sediment diversion has resulted in morphodynamic changes in the Mississippi River.…”
Section: Implications Of the Theoretical Analysis For The Analysis Of...mentioning
confidence: 86%
“…The objective of this study was to simulate a range of possible bank erosion responses to various flow scenarios in comparison to actual flows. Other OMAR Assessment tasks have concluded that the Atchafalaya River is in a state of relative equilibrium and not undergoing systemic widening (Lauth et al 2022). The measured bank erosion used for calibration data is a result of natural processes of bank erosion and not seen as a symptom of a larger, systemic issue.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the OMAR Assessment, there was assumed to be a system-wide problem with the Atchafalaya River widening due to toe scour and subsequent bank failure. The geomorphology task within the OMAR study found that while there was a period of dramatic widening in the early to mid-twentieth century, this behavior has tapered off in the recent decades (Lauth et al 2022). The trends in width show very slight increases to no change from 1976 to 2019 and overall stability within the reach between Simmesport, LA, and the Whiskey Bay Pilot Channel with very slight periods of erosion and deposition over the aforementioned time period (Little and Biedenharn 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The specific gage and survey data analyses from the OMAR geomorphic assessment (Task 2) (Lauth et al 2022) can provide a measure of confidence to the HEC-6T simulated results. The geomorphic study and the HEC-6T historical simulation are in relative agreement that the Outflow Channel downstream from the Hydropower Outflow Channel and the Atchafalaya River at Simmesport are in dynamic equilibrium.…”
Section: Adjustment Of Outflow Channel Sediment Inflowmentioning
confidence: 99%